Metal [Zn(II), Cd(II)], 1,10-phenanthroline containing coordination polymers constructed on the skeleton of polycarboxylates: synthesis, characterization, microstructural, and CO2 gas adsorption studies - Yadav, Pramod Kumar; Kumari, Niraj; Pachfule, Pradip; Banerjee, Rahul; Mishra, Lallan (Crystal Growth & Design, 2012)
{Four new coordination polymers have been obtained by the reaction of metal [Zn(II), Cd(II)], 1,10-phenanthroline separately with two carboxylic acids, [biphenyl-4,4'-dicarboxylic acid (4,4'-H(2)BDA),and 4,4'-azodibenzoic acid (4,4'-H(2)ADA)]. The crystal structures of the resulting complexes of type {[Zn(4,4'-BDA)(Phen)(2)center dot HCON(CH3)(2)}(n) (1), {[Cd(4,4'-BDA)(Phen)](2)center dot H2O\